2021
DOI: 10.3389/fmicb.2021.707609
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cabrialesii BH5 Protects Tomato Plants Against Botrytis cinerea by Production of Specific Antifungal Compounds

Abstract: The gray mold caused by the phytopathogen Botrytis cinerea presents a threat to global food security. For the biological regulation of several plant diseases, Bacillus species have been extensively studied. In this work, we explore the ability of a bacterial strain, Bacillus cabrialesii BH5, that was isolated from tomato rhizosphere soil, to control the fungal pathogen B. cinerea. Strain B. cabrialesii BH5 showed a strong antifungal activity against B. cinerea. A compound was isolated and identified as a cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Among the reported beneficial microorganisms and biological agents, Bacillus spp. has been widely applied in the management of various plant diseases ( Shafi et al, 2017 ; Yang et al, 2020 ; Zhou et al, 2021 ). Here, phylogenetic analysis indicated that SYL-3 showed high sequence identity and clustered closely with species B. velezensis .…”
Section: Discussionmentioning
confidence: 99%
“…Among the reported beneficial microorganisms and biological agents, Bacillus spp. has been widely applied in the management of various plant diseases ( Shafi et al, 2017 ; Yang et al, 2020 ; Zhou et al, 2021 ). Here, phylogenetic analysis indicated that SYL-3 showed high sequence identity and clustered closely with species B. velezensis .…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus species (such as B. subtilis , B. amyloliquefaciens , B. velezensis , B. nakamurai , and B. siamensis ) possess a broad spectrum of antifungal activities and can effectively inhibit various fungal pathogens, which highlighting the applicable potential of Bacillus species in controlling the development of fruit postharvest fungal diseases, such as peach brown rot (caused by Monilinia fructicola or Monilinia laxa ) [31], ring rot (caused by Botryosphaeria dothidea ) [32], gray mold (caused by Botrytis cinereal ) [33], anthracnose (caused by C. gloeosporioides or C . acutatum ) [34], citrus decay (caused by Penicillium digitatum , P. expansum , or P. italicum ) [35].…”
Section: Discussionmentioning
confidence: 99%
“…The iturin families are naturally antifungal agents displaying strong activities against Fusarium graminearum, C. gloeosporioides, C. acutatum, Saccaromyces cerevisiae, Alternaria alternate, B. cinerea, Fusarium oxysporum, and Rhizoctonia solani by damaging the plasma membranes to form a large pore and inhibiting hypha growth [43][44][45]. Fengycins are known to exhibit antimicrobial activities against Rolani stolonifera [46,47], F. oxysporum [48], F. graminearum [49], M. fructicola [50], Rhizomucor variabilis [51], Candida albicans [52], Sclerotinia sclerotiorum [53], B. dothidea [32], B. cinerea [33], C. gloeosporioides, C. musae [54], C. acutatum [34], and Ralstonia solanacearum [22] via destruction of the plasma membranes or the cell wall, cell lysis, inhibition of DNA synthesis and accumulation of ROS, consequently causing cell death. Most of surfactins exert their strong antibacterial activities against Staphylococcus aureus, Enterobacter sp.…”
Section: Effects Of the Purified Lipopeptides Against C Acutatum Ex Situmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, chemical control has been the most effective strategy for strawberry gray mold control for years (de Moura et al, 2021;Fontana et al, 2021;Zhou et al, 2021). However, frequent and large-scale use of numerous fungicides leads to the increasingly serious "3R" problems (Resistance, Resurgence and Residue) (de Moura et al, 2021).…”
Section: Introductionmentioning
confidence: 99%